PENGARUH PENERAPAN MODEL TREFFINGER TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XII JURUSAN AKUNTANSI DI SMK YADIKA NATAR 2019 - Fitria, Nur; Zainal, Vetri Yanti (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The background of this research was the existence of problem in which the gain of students learning outcome on Accounting subjects is low. The low learning outcomes due there are factors where one of the factors is the teacher still uses a method that is less varied which causes learning to be passive and low interest in learning of the students. This research uses experimental method that is by using method Treffinger. From hypothesis testing using t test statistic formula to know whether there is influence of aplication of learning method learning cycle. After testing of hypothesis on test of different of two mean and calculation of data of accounting learning result by using statistic formula, hence in can t hit 4,30 and t tab 2,00 at 5% significant level so that proved that t hit > t tab. With so it can be concluded “there is influence of learning method of Treffinger to students Accounting learning result of class XII SMK Yadika Natar year lesson 2019. Judging from the mean score of the students, the experimental class 84,56 and the control class had a average value of x = 72, 40. So the average students accounting learning outcomes using Treffinger method are higher than students using conventional learning methods